COMPARISON OF ANTIBODY TITERS IN BROILERS GIVEN GREEN MENIRAN EXTRACT AT DIFFERENT DOSES FOR TWO WEEKS BEFORE NEWCASTLE DISEASE BOOSTER VACCINATION - Dewa Kade Agung Hendra Putra Dinata; Ida Bagus Kade Suardana Suardana; I Ketut Suada; Ni Luh Eka Setiasih; I Made Kardena; Tjokorda Sari Nindhia (Buletin Veteriner Udayana, 2025)
Newcastle Disease (ND) is a viral disease that affects poultry, including broilers. One of the preventive measures is vaccination; however, its effectiveness remains suboptimal, necessitating an alternative approach such as green meniran (Phyllanthus niruri Linn.) extract to enhance antibody titers. This study aims to determine the differences in antibody titers in broilers administered green meniran extract at different doses for two weeks before the ND booster vaccination. The study involved 30 broilers aged 1 to 32 days. The experimental design followed a Completely Randomized Design with a hierarchical pattern consisting of three treatment groups. Serum samples were collected one day before the ND booster vaccination (17 days old), oneweek post-booster vaccination (25 days old), and two weeks post-booster vaccination (32 days old). The serum samples were tested using the Hemagglutination Inhibition (HI) assay. Data were analyzed using Analysis of Variance (ANOVA) and regression analysis. ANOVA results showed that the treatment group (P2) receiving green meniran extract at a dose of 6 mg/kg BW/day exhibited a significant increase (P<0.05) compared to the treatment group (P1) receiving 4 mg/kg BW/day. Regression analysis indicated that each group experienced an increase in antibody titers up to the fourth week post-booster vaccination. The findings suggest that different sampling times significantly (P<0.05) influenced the antibody titers formed. In conclusion, green meniran extract as a natural immunostimulator can enhance the immune response in broiler chickens. The combination of green meniran extract at doses of 4 mg/kg BW/day and 6 mg/kg BW/day for two weeks with ND booster vaccination proved to be more effective in increasing ND antibody titers in broilers than vaccination alone.